Dampak Penggunaan Perangkat Mobile dalam Mendukung Kegiatan Pembelajaran Mandiri Siswa Kelas IX di SMP PGRI Rancaekek - Santi Puspa Oktaviane; Patah Herwanto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The development of information and communication technology, especially mobile devices, has changed the learning landscape significantly. This research aims to examine the impact of using mobile devices in supporting the independent learning activities of class IX students at SMP PGRI Rancaekek. This research is motivated by the increasingly widespread ownership of mobile devices among students and their potential to increase motivation and learning effectiveness. The research method used is descriptive qualitative with data collection through observation, interviews and documentation. The research subjects were class IX students and subject teachers. Data analysis was carried out inductively to identify emerging themes related to the impact of mobile device use. The research results show that the use of mobile devices has a positive impact on students' independent learning activities. Mobile devices provide easier access to various learning resources, facilitate communication between students and teachers, and increase learning motivation. However, the research also found several challenges, such as dependency on devices, lack of monitoring of use, and gaps in access. The implication of this research is the importance of integrating the use of mobile devices in the learning process. Schools need to develop clear policies regarding the use of mobile devices, provide training for teachers, and ensure equitable access for all students. In addition, further research is needed to examine the long-term impact of mobile device use on student learning achievement.